Development And Validation Of Rp-Hplc Method For Estimation Of Rifapentine. - D.Pawar, Sonali; D. Rakibe, Vaishali; T.Daware, Kavita; D.Pawar, Snehal (Journal of Neonatal Surgery, 2025)
Reverse-phase high-performance liquid chromatography was developed and validated as a simple, accurate, precise and sensitive method for estimation of Delamanid in bulk and pharmaceutical dosage form. Chromatography was carried out on C18 column using a mixture of HPLC grade Methanol; 0.1% ortho phosphoric acid (81/19) as the mobile phase at a flow rate of 1.1 mL/min. The detection was carried out at 222 nm. It was determined that the retention time was 4.278 ± 0.12 min. The method produces linear response in the concentration range of 10 to 50 µg/mL of Rifapentine. The method precision for the determination of assay was below 2%RSD. Accuracy was found in the limit. The method is useful in the quality control of bulk and pharmaceutical dosage form.